Putative actin genes in the macronucleus of Oxytricha fallax. - Kaine, B P (1980)
Previous work has shown that the macronuclear DNA of the hypotrichous ciliate Oxytricha fallax is arranged as short achromosomal pieces, 22 to 0.5 kilobase pairs (kb) in length. Micronuclear DNA has a typical chromosomal organization. Macronuclear DNA is derived from micronuclear DNA through a process of polytene chromosome fragmentation with a resultant decrease in DNA sequence complexity. Three putative actin genes have been identified in macronuclear DNA by using a cloned yeast actin gene as a hybridization probe. A restriction fragment of the yeast gene containing both actin coding and noncoding DNA hybridizes strongly to two macronuclear DNA pieces, 1.6 and 1.4 kb in length, and weakly to a 1.2-kb piece. The entire 1.6-kb piece has been cloned in plasmid pBR322 and the resulting recombinant plasmid has been designated pOfACT(1.6). The 1.6-kb pOfACT(1.6) insert hybridizes only to those restriction fragments of the yeast actin gene containing actin coding sequences. When hybridized to macronuclear DNA under conditions that allow the yeast probe to hybridize to all three macronuclear pieces, the pOfACT(1.6) insert hybridizes only to the 1.6-kb piece. Under less stringent conditions the insert also hybridizes to the 1.4-kb piece, but it shows no hybridization to the 1.2-kb DNA. The three macronuclear pieces homologous to the yeast actin gene thus differ in sequence and are interpreted as a related family of actin genes. Each of these pieces could accommodate an actin coding sequence, which in yeast, Dictyostelium discoideum, and Drosophila melanogaster is 1.1 kb, and an additional 0.1-0.5 kb of noncoding DNA.